Implementing Robots in Defence Through Motion Capture with Mixed Reality - Yellamma, Pachipala; Madhav Bharadwaj, Ch; R. Krishna Sai, K; Narasimham, Challa (International Journal of Engineering and Technology, 2018)
Our soldiers are fighting for us, risking their lives and people working in mines spoiling their health. In this paper we will see how we will implement the technology of mixed reality and motion capture will give solutions for replacing humans with robots. We can save a lot of lot of human lives and it will be more cost efficient. As on today we are implementing motion capture in analyzing the responses of military soldiers to test their capabilities and doing animations in movies. So let us extend the existing features to implement a remote robot control system that allows us to replace humans with robots.Â Â